Specific Forms of Organizing Technology Classes: Bentuk Spesifik Penyelenggaraan Kelas Teknologi - Ganieva Munosibhon Murodjon (Universitas Muhammadiyah Sidoarjo, 2022)
This article explores the significance of labor education in cultivating a constructive attitude towards work, acting as the cornerstone of schooling and extracurricular activities, thereby strengthening the vital connection between school and life. The study aims to investigate the primary educational objectives, methods, results, and implications associated with psychologically and practically preparing students for the workforce. The research findings underscore the importance of labor education in fostering a positive work ethic, enhancing students' preparedness for future employment, and facilitating their successful integration into the labor market. The implications of this study have far-reaching implications for educational institutions worldwide, offering valuable insights into optimizing curricula and extracurricular activities to effectively equip students with the necessary skills and attitudes for successful careers. Highlights: Labor education as a core component: This article emphasizes labor education as a fundamental aspect of schooling and extracurricular activities, highlighting its central role in shaping students' attitudes towards work. Psychological preparation for work: The study underscores the significance of psychologically preparing students for the workforce, recognizing it as a crucial educational task of schools. Implications for successful integration: The research findings have far-reaching implications, emphasizing the importance of labor education in facilitating students' successful integration into the labor market, equipping them with the necessary skills and attitudes for future careers. Keywords: labor education, attitude to work, schooling, extracurricular activities, psychological preparation